1995
DOI: 10.1590/s0074-02761995000300011
|View full text |Cite
|
Sign up to set email alerts
|

The development of species of Leishmania Ross, 1903 in Lutzomyia longipalpis (Lutz & Neiva, 1912)

Abstract: The development of four isolates of Leishmania from foci of American cutaneous leishmaniasis was studied in Lutzomyia longipalpis. The suggestion that the differences in the development of the Leishmania in the invertebrate host are of great taxonomic significance was confirmed. The pattern of development of three strains was typical of parasites of the subgenus Leishmania, the other was similar to Leishmania of the subgenus Viannia. The identification of the strains using other criteria is in agreement with b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
6
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 0 publications
2
6
0
1
Order By: Relevance
“…A higher infection rate was observed after exposure of the sand fly to L. amazonensis (37%) and L. guyanensis (100%). Similar results were observed by [47], with two isolates of L. amazonensis presenting more than 60% of infection in Lu. longipalpis and one isolate of L. braziliensis presenting only 5% of infection rate.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…A higher infection rate was observed after exposure of the sand fly to L. amazonensis (37%) and L. guyanensis (100%). Similar results were observed by [47], with two isolates of L. amazonensis presenting more than 60% of infection in Lu. longipalpis and one isolate of L. braziliensis presenting only 5% of infection rate.…”
Section: Discussionsupporting
confidence: 89%
“…Studies on experimental infections in sand flies with different Leishmania species suggest that Lu. longipalpis is a permissive vector, which support the development of different Leishmania species [45-47]. The susceptibility of Lu.…”
Section: Discussionmentioning
confidence: 99%
“…However, this is not sufficient to incriminate this sand fly as a vector of species of Leishmania that cause ACL, despite the fact that several studies on experimental infections showed high susceptibility of Lu . longipalpis to different Leishmania species [ 53 , 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Of the various morphological forms of leishmanial cells that have been reported, rosettes have largely been ignored, being considered artifacts (Mehlhorn and Armstrong 2001; Schuster and Sullivan 2002) despite their repeated observation within the midgut of sandfly and flea insect vectors (Feliciangeli et al 1988; Gontijo et al 1995; Lainson and Shaw 1973; Leishman 1911), and the precise orientation of promastigote cells with their flagella directed toward the center of the rosette, an arrangement with obvious resemblance to the pairing of Chlamydomonas cells during the mating process (Pan and Snell 2000). Recently, genetic recombination in Leishmania has been demonstrated, providing evidence that a sexual cycle does exist for these organisms (Akopyants et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Of the various morphological forms of Leishmania that have thus far been reported, rosettes have largely been ignored, despite their repeated observation in the midgut of insect vectors (Feliciangeli, Reyes, and Limongi 1988; Gontijo et al 1995; Lainson and Shaw 1973; Leishman 1911). Rosettes have been considered characteristic of a “feeding frenzy” (Pommerville and Alcamo 2004), the result of delayed multiplication (Mehlhorn and Armstrong 2001), or an artifact of flagellar entanglement during in vitro cultivation (Mehlhorn and Armstrong 2001; Schuster and Sullivan 2002).…”
mentioning
confidence: 99%